Comparison of Conventional versus Molecular Methods to Identify Escherichia coli Isolated from Stool Samples - Lawani-Luwaj, Ebidor; Tolulope, Alade; Emenike, Miracle (British Journal of Healthcare and Medical Research, 2023)
The contemporary means of identifying bacteria are mainly phenotypic tests. Nevertheless, phenotypic tests have their likely characteristic problems. Studies on bacteria isolates have progressed from cultural characterisation, serological, antibiotic resistance profiling, and molecular and genetic engineering to sequencing. This study compared traditional culture algorithms with molecular techniques to identify and characterise Escherichia coli isolated from 50 stool samples. The bacterial isolates were analysed with standard conventional methods, and the 16S rRNA gene was amplified using Polymerase Chain Reaction (PCR). Out of the 50 samples. 15(45.5%) were conventionally identified as Escherichia coli. Representative E.coIi isolates were then sequenced, and the genotypic identification showed that one of the isolates was Enterobacter cloacae, not Escherichia coli. Molecular biology techniques can avoid misidentification with the conventional method across various microorganisms.